Health Belief Model and Contraceptive Choice Among High-Risk Women: A Cross-Sectional Study - Hayunda Shasta Deasy; Nurul Pujiastuti; Sunaeni; Didien Ika Setyarini (Jurnal Kebidanan Midwiferia, 2026)
Inappropriate contraceptive choice among high-risk women of reproductive age (WRA) may increase the risk of unintended pregnancy and adverse maternal outcomes. Individual perceptions and beliefs regarding health risks and preventive actions, as described in the Health Belief Model (HBM), may influence contraceptive choice. However, evidence regarding the relationship between HBM components and contraceptive choice among high-risk WRA at the community level remains limited. This study aimed to analyze the relationship between Health Belief Model components and contraceptive choice among high-risk WRA in Mulyorejo Village, Sukun Subdistrict, Malang City. This study used a quantitative correlational design with a cross-sectional approach conducted from November 2024 to January 2025. A total of 64 respondents were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using the Spearman Rank correlation test with a significance level of 0.05. The results showed statistically significant relationships between all HBM components and contraceptive choice among high-risk WRA. Perceived susceptibility was associated with contraceptive choice (r = 0.301; p = 0.016), as were perceived severity (r = 0.349; p = 0.005), perceived benefits (r = 0.314; p = 0.011), perceived barriers (r = 0.313; p = 0.012), and cues to action (r = 0.307; p = 0.014). All correlations were categorized as low to moderate. The findings indicate that HBM components play an important role in influencing contraceptive choice among high-risk WRA. Strengthening women’s perceptions of pregnancy risk and improving counseling strategies may support appropriate contraceptive selection and improve reproductive health outcomes.